The practice of science and technology communication in science museums - Rennie, Leonie (Routledge, 2012)
People choose to participate in science-related activities in informal environments because the experiences or their outcomes are inherently interesting or useful to them. Thus the communication of science in informal environments is characterised by choice. People may choose to notice and accept the opportunities to learn about science, or they may not. Most informal sources of science, including museums and similar institutions, usually present their information in story form to facilitate the interest, and hence engagement, of the intended audience. Developing that science story is a way of selecting, packaging and presenting science information in a way that the intended audience can understand and interpret it, according to their own needs and experience. This chapter examines how such science stories may be developed and provides research-based examples from science museums and science centres to illustrate how the stories are received. The chapter concludes with a discussion of the issues exhibit designers need to consider about the effective communication of science.